Home fires [videorecording (DVD)]. - Bond, Samantha, 1962-; Annis, Francesca, 1945-; Calbraith, Clare, 1974- (Masterpiece., 2015)
Bitter rivals fight for control of the Women's Institute in a rural English town as it struggles with the onset of World War II. Separated from husbands, fathers, sons and brothers for years at a time, some permanently, they find themselves under extraordinary pressures in a rapidly fragmenting world.